English, asked by mavisukhdeep4, 1 year ago

factorisation
qudratic equation by
2x²+x-6=0​

Answers

Answered by sujalmishragenius
0

Explanation:

HOPE IT HELPS YOU.

follow me..

Attachments:
Answered by raushan6198
2

Explanation:

2 {x}^{2}  + x - 6 = 0 \\  =  > 2 {x}^{2}  + 4x - 3x  - 6 = 0 \\  =  > 2x(x + 2) - 3(x  +  2) = 0 \\  =  > (2x - 3)(x + 2) = 0 \\  =  > 2x - 3 =  0 \:  \:  \:  \:  \:  \:  \:  |  \:  \: x + 2 = 0 \\  =  > 2x = 3 \:  \:  \:  \:  |  \: x =  - 2 \\  =  > x =  \frac{3}{2}

Similar questions